Contracting Sugarcane Farming in Global Agricultural Value Chains in Eastern Africa: Debates, Dynamics, and Struggles. (April 2019) - Martiniello, Giuliano; Azambuja, Ricardo
Integrating smallholders within global agricultural value chains through contract farming has regained momentum in the development agenda, particularly in Africa. Governments, corporate agri-business, and global development institutions have embraced sugarcane as a suitable commodity to promote the integration of smallholders within commercial agricultural circuits so as to improve the prospects of rural development and reduce rural poverty. Influenced by the new institutional economics paradigm, win-win scenarios in which agribusiness companies and smallholders reciprocally benefit—the former by getting regular and standardized quantities of produce; the latter through secure access to the market—are advocated. However, little evidence of success in contract farming has been provided. By exploring the socio-ecological implications of contract farming within two major agro-industrial complexes (in Uganda and Tanzania), we demonstrate that the incorporation of smallholders in these schemes is spearheading dispossession from below, selection of most competitive producers, ecological degradation, social differentiation, and conflict.